The nine elements of a sustainable campus - Thomashow, Mitchell (The MIT Press, 2014)
A college campus offers an ideal setting for exploring and practicing sustainability. Colleges and universities offer our best hope for raising awareness about the climate crisis and the dire threat it poses to the planet. They provide opportunities for both research and implementation; they have the capacity to engage students, staff, and faculty in collaborative enterprises that inspire campus transformation; they take the idea of legacy seriously. But most college and university administrations need guidance on the path to sustainability. In The Nine Elements of a Sustainable Campus, Mitchell Thomashow, a former college president, provides just that.